2008
DOI: 10.1007/s10658-008-9315-0
|View full text |Cite
|
Sign up to set email alerts
|

A during-infection spray strategy using sulphur compounds, copper, silicon and a new formulation of potassium bicarbonate for primary scab control in organic apple production

Abstract: In a field experiment conducted over two growing seasons, the effectiveness and phytotoxicity of inorganic fungicides such as sulphur, lime sulphur, copper, silicon and Armicarb (a new formulation of potassium bicarbonate) was compared with water for the control of primary apple scab infections in Belgium on high, medium and low scab-susceptible cultivars (cvs 'Pinova', 'Pirouette' and 'Reinette des Capucins', respectively). In order to drastically reduce the amount of fungicide applied in the orchard, two app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 26 publications
1
19
0
1
Order By: Relevance
“…Potassium bicarbonate and wettable sulphur used separately also reduced the attack on the leaves, but in the smaller scale. 118 As noted in previous studies (Holb et al, 2003;Jamar et al, 2008;Jamar et al, 2010)the treatments applied against apple scab and powdery mildew, after each rain, had several important advantages: no washing effect of products due to the rain; high effectiveness of treatments on spores in germinating phase; prevent new infections.…”
Section: The Influence Of Different Products Against Powdery Mildew Amentioning
confidence: 89%
See 1 more Smart Citation
“…Potassium bicarbonate and wettable sulphur used separately also reduced the attack on the leaves, but in the smaller scale. 118 As noted in previous studies (Holb et al, 2003;Jamar et al, 2008;Jamar et al, 2010)the treatments applied against apple scab and powdery mildew, after each rain, had several important advantages: no washing effect of products due to the rain; high effectiveness of treatments on spores in germinating phase; prevent new infections.…”
Section: The Influence Of Different Products Against Powdery Mildew Amentioning
confidence: 89%
“…The efficiency of bicarbonate salts in controlling apple scab reported in previous studies (Schulze et al, 2003;Ilhan et al, 2006;Tamm et al, 2006;Jamar and Lateur, 2007;Jamar et al, 2007aJamar et al, , 2007bJamar et al, , 2008Jamar et al, , 2010 suggests that this compound could be introduced in apple disease management, with the remark that is not to be used alone, but with other active compounds. Even bicarbonates seem to be effective against scab and powdery mildew, but a long lasting effect cannot be expected, because they are unstable compounds that are highly water-soluble and easily washed off the leaves by a small amount of precipitation (Jamar et al, 2010).…”
Section: The Influence Of Different Products Against Powdery Mildew Amentioning
confidence: 92%
“…entre los factores ambientales que precedieron al ataque de los patógenos foliares, se encontró que la alta precipitación precedió entre 1 y 2 meses la aparición de los síntomas (Figura 10). La precipitación se encuentra asociada con las primeras infecciones (Jamar et al, 2008), determinando el desencadenamiento de la aparición de brotes de las enfermedades de las plantas. Figura 7.…”
Section: Datos Climáticosunclassified
“…x p = pyraclostrobin combined with b = boscalid. w Fungicide common names, brand names, formulations used, and manufacturer: basic copper sulfate (Cuprofix Disperss 20DF; Cerexagri, Inc., King of Prussia, PA, in 2007and Cuprofix Ultra 40 Disperss in 2008and 2009; chlorothalonil (Echo 720; Sipcam Agro USA, Inc., Roswell, GA, in 2007, 2008, and 2009 and Equus 720 SST; Makhteshim Agan North America, Inc., Raleigh, NC, in 2009); fenbuconazole (Indar 75WSP; Dow AgroSciences, LLC, Indianapolis, IN); pyraclostrobin + boscalid (Pristine, BASF Corp., Research Triangle Park, NC); tebuconazole (Elite 45DF; Bayer CropScience, Research Triangle Park, NC); trifloxystrobin (Gem 500SC; Bayer CropScience, Research Triangle Park, NC). Amounts of copper refer to metallic copper equivalent applied.…”
Section: Plantmentioning
confidence: 99%
“…McManus et al (2007) concluded that applications of copper-based fungicides did not lead to more defoliation assessed at the time of fruit harvest compared with CLS management programs relying solely on synthetic fungicides. However, the effects of copper-based fungicides on fruit quality are not well understood because reported results are contradictory and the metrics used to evaluate fruit quantity and quality have differed among studies (Holb and Schnabel, 2005;Jamar et al, 2008;Keitt et al, 1937;Lalancette and McFarland, 2007;Palmer et al, 2003). Consequently, the overall aim of the current study was to determine if postbloom applications of copper-based fungicides and leaf bronzing are deleterious to tart cherry fruit.…”
mentioning
confidence: 96%